(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Ensuring the quality of teaching foreign languages to the young generation, fundamentally improving the system of training specialists who can speak foreign languages fluently, training mature personnel who meet world educational standards by mastering foreign languages in our country is one of the goals of the education reform. The knowledge, creativity of the teacher, the ability to arouse students’ love for their subject, and the establishment of a cooperative relationship with the student are the requirements of the current era. The decision to further develop foreign language teaching, implement measures to improve the level and quality of training of qualified teachers who have a high level of foreign language skills for general education schools, vocational colleges and academic lyceums, higher education institutions in accordance with international standards. was adopted in order to provide. At the same time, it should be said that every language being studied has its own rules and secrets. In order to become a mature specialist who meets international standards, the learner is required not to overlook the most subtle layers of the language.